Mediation and moderation roles of resilience capacity in the shock–food-security nexus in northern Ghana - Ansah, I.G.K.; Kotu, Bekele Hundie; Manda, J.; Muthoni, F.K.; Azzarri, Carlo (Elsevier, 2023)
This paper examines how resilience capacity mediates or moderates the relationship between weather shocks and household food security based on two waves of farm household survey and satellite-based weather data in northern Ghana and applying econometric models. Results show that resilience capacity moderate or mediates the negative effects of heat stress and drought on food security. However, the mediating role of resilience capacity in the shock-food security nexus is more stable and stronger than its moderating role. A standard deviation (SD) increase in heat stress reduces household food consumption by 0.71 SD, but resilience capacity effectively moderates this effect by approximately 0.61 SD. For drought, household food consumption is reduced by 0.67 SD, but resilience capacity effectively dampens this negative effect by approximately 0.60 SD. The mediation results, on the other hand, indicate that 537% of the total effect of heat stress on household calorie consumption is explained by the indirect effect through resilience capacity. Similarly, resilience capacity mediates about 74% of the total effect of heat stress on household food consumption. These results suggest that strategies that help improve resilience capacity, such as the adoption of sustainable intensification practices, are critical in enhancing food security in northern Ghana.